pone.0323574.t014 - Research on two-stage dynamic optimization model and algorithm for agricultural products joint distribution network based on vehicles and customers sharing under data-driven - Meilin Zhu (688698) (2025)
pone.0323574.t014 - Research on two-stage dynamic optimization model and algorithm for agricultural products joint distribution network based on vehicles and customers sharing under data-driven